Perspectives on conservation grazing : The need for monitoring and communication - Millett, Jonathan; van Soest, Maud A.J.; Edmondson, Sally; Gahan, Peter; Hunt, Natalie; Mercer, Dave; O'Brien, James; Smith, Barry; Webster, Charlotte; Dwyer, Ciara (Ecological Solutions and Evidence, 2025)
Conservation grazing is widely used to manage open ecosystems, but inconsistent definitions and inadequate reporting of grazing patterns hinder effective communication among researchers, practitioners and policymakers, limiting the understanding and success of conservation grazing regimes. We demonstrate detailed measurement of the grazing pattern (comprising timing, intensity, duration and frequency) in management units within a single nature recovery site—Ainsdale Sand Dunes National Nature Reserve, in the United Kingdom. We highlight the potential value of using existing records of livestock movements to create a detailed picture of how the pattern of grazing varies between management units and over time. The pattern of grazing at Ainsdale Sand Dunes National Nature Reserve (Ainsdale NNR) has changed over time due to responsive management approaches. These management approaches also result in differences between grazing enclosures. We recommend that standard definitions are agreed upon to unify terminology for conservation grazing patterns and regimes. This will improve clarity, reporting and monitoring. We encourage sites to record daily livestock movements to track grazing patterns and plant communities, to monitor their impacts. We propose a common framework for describing grazing patterns to enable the effective use of data and allow comparisons across other sites. Practical implication. Bridging the gap between academics and land managers is essential, as limited staff, resources, time and in-house expertise often prevent managers from moving beyond data collection to effective data use in decision-making. Strengthening this connection will enhance the monitoring, analysis and communication of the analysis of grazing patterns, and support improved nature recovery outcomes.
Publisher Copyright: © 2025 The Author(s). Ecological Solutions and Evidence published by John Wiley & Sons Ltd on behalf of British Ecological Society.
Keywords: coastal sand dune; conservation grazing; livestock; nature recovery